Effect of Gliding Arc Plasma Jet on the Mycobiota and Deoxynivalenol Levels in Naturally Contaminated Barley Grains - Chiappim, William [UNESP]; de Paula Bernardes, Vanessa; Almeida, Naara Aparecida; Pereira, Viviane Lopes; Bragotto, Adriana Pavesi Arisseto; Cerqueira, Maristela Barnes Rodrigues; Furlong, Eliana Badiale; Pessoa, Rodrigo; Rocha, Liliana Oliveira (MDPI, 2023)
Fusarium graminearum and Fusarium meridionale are primary contaminants of barley, capable of producing several mycotoxins, mainly type B trichothecenes and zearalenone. Cold plasma decontamination has been gaining prominence, seeking to control the fungal and mycotoxin contamination of food and feed and to improve product quality. To reach this objective, the present study was divided into two parts. In the first part, F. meridionale and F. graminearum strains were exposed to gliding arc plasma jet (GAPJ). Cell viability tests showed the inactivation of F. meridionale after 15-min treatment, whereas F. graminearum showed to be resistant. In the second part, barley grains were treated by GAPJ for 10, 20, and 30 min, demonstrating a reduction of about 2 log CFU/g of the barley’s mycobiota, composed of yeasts, strains belonging to the F. graminearum species complex, Alternaria, and Aspergillus. A decrease in DON levels (up to 89%) was observed after exposure for 20 min. However, an increase in the toxin Deoxynivalenol-3-glucoside (D3G) was observed in barley grains, indicating a conversion of DON to D3G.
Keywords: cold plasma; decontamination; Fusarium graminearum; Fusarium meridionale; masked mycotoxins; mycotoxins; QuEChERS